Source or target first? Comparison of two post-editing strategies with translation students - Volkart, Lise; Girletti, Sabrina; Gerlach, Johanna; Mutal, Jonathan David; Bouillon, Pierrette (Journal of data mining and digital humanities, 2022)
We conducted an experiment with translation students to assess the influence of two different post-editing (PE) strategies (reading the source segment or the target segment first) on three aspects: PE time, ratio of corrected errors and number of optional modifications per word. Our results showed that the strategy that is adopted has no influence on the PE time or ratio of corrected errors. However, it does have an influence on the number of optional modifications per word. Two other thought-provoking observations emerged from this study: first, the ratio of corrected errors showed that, on average, students correct only half of the MT errors, which underlines the need for PE practice. Second, the time logs of the experiment showed that when students are not forced to read the source segment first, they tend to neglect the source segment and almost do monolingual PE. This experiment provides new insight relevant to PE teaching as well as the designing of PE environments.